PENANAMAN MODAL ASING DAN PERTUMBUHAN INDUSTRI DI ASEAN(6), CHINA, INDIA, DAN KOREA SELATAN 1999-2004 - Sri Yani Kusumastuti (Journal of Indonesian Economy and Business (JIEB), 2008)
The objective of this study is to shed light on the determinants of foreign direct investment (FDI) in Asian developing countries and their impact on industrial growth. In order to undertake it, we perform an econometric model based in panel data analysis for 9 countries (such as ASEAN 6, China, India, and Korea) for the 1999-2004 periods. We estimate the simultaneous equation using panel data estimation with fixed effect and random effect. Among the major conclusions we have that the FDI is determined by country risk and variables related to macroeconomic indicators like inflation, risk, economy’s degree of openness and average rate of economic growth, average rate of world economic growth, and level of education. The results also show that the FDI has been closely associated with corruption perception index and performance of FDI in the past. However the other variables, such as the global competitive index and rank of investment performance and potential have no more influential on FDI inflows. Finally, we have that the growth of industrial sector is positively related to the FDI inflows.